Cardiovascular Disease Risk Score Correlates with Glomerular Filtration Rate in Hemodialysis Patients: A Cross-Sectional Pilot Study - Nabil Hajar; Bintang Adhiyoso Wicaksono; Zulfachmi Wahab; Shofa Chasani; Galih Prakasa Adhyatma; Nabila Nuralya Joveazhari; Zeidan Ahmad Fahdalhaq (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Chronic kidney disease is closely linked to an elevated risk of cardiovascular morbidity and mortality, particularly among patients undergoing hemodialysis. This study aimed to examine the relationship between cardiovascular disease risk scores and renal function using an empirical cross-sectional design. A total of 72 eligible patients receiving hemodialysis were assessed using the World Health Organization Risk Prediction Chart for Southeast Asia Region B to estimate 10-year cardiovascular risk. Renal function was evaluated using the Cockcroft–Gault equation to determine glomerular filtration rate values. Descriptive analysis demonstrated a predominance of high cardiovascular risk categories alongside severely reduced renal function. Inferential analysis using the Spearman rank correlation test revealed a statistically significant inverse relationship between cardiovascular risk score and glomerular filtration rate (r = -0.637; p = 0.000). These findings indicate that higher cardiovascular risk is associated with more severe renal impairment. The results support the integration of cardiovascular risk assessment into routine clinical evaluation of patients with chronic kidney disease undergoing hemodialysis to improve early risk stratification and management strategies.